2022
DOI: 10.5194/hess-2022-2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flood generation: process patterns from the raindrop to the ocean

Abstract: Abstract. This article reviews river flood generation processes and flow paths across space scales. The scale steps include the pore, profile, hillslope, catchment, regional and continental scales, representing a scale range of a total of 10 orders of magnitude. Although the processes differ between the scales, there are notable similarities. At all scales, there are media patterns that control the flow of water, and are themselves influenced by the flow of water. The processes are therefore not spatially rand… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…However, at subcontinental scales, catchment characteristics become the primary control since their spatial variance is higher than that of climate. The scaling properties of low flows differ fundamentally from those of floods (Blöschl, 2022;Viglione et al, 2016). While flood scaling is linked with catchment size in which different hydrological processes predominate (Blöschl, 2022), the low flow scaling found in this study is related to the variables' spatial variance captured by the model.…”
Section: Scaling Properties Of Low Flowsmentioning
confidence: 59%
“…However, at subcontinental scales, catchment characteristics become the primary control since their spatial variance is higher than that of climate. The scaling properties of low flows differ fundamentally from those of floods (Blöschl, 2022;Viglione et al, 2016). While flood scaling is linked with catchment size in which different hydrological processes predominate (Blöschl, 2022), the low flow scaling found in this study is related to the variables' spatial variance captured by the model.…”
Section: Scaling Properties Of Low Flowsmentioning
confidence: 59%
“…This was necessary because the flood generation mechanism for small and large catchments are different (Blöschl, 2022b). Small catchments are more sensitive to the infiltration excess runoff, while large catchments are sensitive to the saturation excess runoff (Blöschl, 2022a). The results showed that in fact there are relations between the surface area and the choice of time-step and hydrology model in the final response of the catchments: First, using a finer time-step in simulations resulting a statically significant increase in the projection of summer-fall flood hazard in the future for the small but not for the large catchment (Figures 8 and 9).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that precipitation is an essential driver of flood events, different reactions from small and large-scale catchments should be expected: for small catchments, the response time is short and the maximum flow peak can be deduced from a storm with a duration equal to the longest flow path in the catchment (Blöschl, 2022a). Given that the short period of convective rainfall matches the residence time of small catchments, these catchments are the most vulnerable to flooding from convective rainfall, which is expected to increase due to climate change (Viglione & Blöschl, 2009;Viglione et al, 2016;Breinl et al, 2021).…”
Section: Introductionmentioning
confidence: 99%